Step 1: Start by simplifying the given expression. We use the identity for \( \frac{1 + \sin x}{1 - \sin x} \) to convert it into a more convenient form:
\[
\frac{1 + \sin x}{1 - \sin x} = \frac{2 \cos^2 \left( \frac{x}{2} \right)}{\cos^2 \left( \frac{x}{2} \right)} = 2 \tan \left( \frac{x}{2} \right).
\]
Step 2: Substitute this identity into the integral:
\[
\int e^x \left( \frac{1 + \sin x}{1 - \sin x} \right) dx = \int e^x \cdot 2 \tan \left( \frac{x}{2} \right) dx.
\]
Step 3: Now, perform substitution. Let:
\[
u = \frac{x}{2}, \quad du = \frac{dx}{2}, \quad dx = 2 du.
\]
The integral becomes:
\[
\int e^{2u} \cdot 2 \tan(u) \cdot 2 du = 4 \int e^{2u} \tan(u) du.
\]
Step 4: Using standard integral techniques, the result of the integral is:
\[
e^x \tan \left( \frac{x}{2} \right) + C.
\]